PROSES HUKUM TINDAK PIDANA KEKERASAN ANAK DALAM KELUARGA DI KOTA SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Noor Yeni Setyawati (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractDomestic violence is a global phenomenon that occurs throughout the centuries of human life, and occurs in all countries. The forms of violence vary, both in the social, cultural, political, economic and educational fields, which are generally victims of women and children in a family environment. Article 44 of Law Number 23 of 2002 states that the government is obliged to provide facilities and carry out comprehensive health efforts for children, so that every child has the optimal health area from the womb.Children as part of the younger generation are the successors of the ideals of the nation's struggle as well as human capital for national development. Article 1 point 1 of law number 23 of 2002 states that child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop, and participate, optimally in accordance with human dignity, and be protected from violence and discrimination.Keywords: Legal Protection for Children, Victims of Domestic Violence